A novel c. 204 Ile68Met germline variant in exon 2 of the mutL homolog 1 gene in a colorectal cancer patient - Vodicka, Pavel; Caja, Fabian; Vymetalkova, Veronika; Prochazka, Pavel; Vodickova, Ludmila; Schwarzova, Lucie; Slyskova, Jana; Kumar, Rajiv; Schneiderova, Michaela (Oncology letters, 2015)
Mutations in the mutL homolog 1 (MLH1) gene are frequent in patients with hereditary non-polyposis colorectal cancer (CRC). The MLH1 gene was screened for mutations in patients with sporadic CRC. The nucleotide sequences for all 19 exons of MLH1 were analyzed by high resolution melting and sequenced in a group of 104 sporadic CRC patients, and the results were verified in a replication group of 1,095 patients and 1,469 controls. Different melting profiles for exon 2 of the MLH1 gene were observed in the germline DNA of one patient. Sequencing of the patient's DNA resulted in the identification of a heterozygous C>G variant at c.204, which resulted in an Ile68Met change in the amino acid. A detailed search of the National Center for Biotechnology Information and the 1000 Genomes databases indicated that the detected variant was unique. According to the SIFT and PolyPhen-2 algorithms, the substitution of Ile to Met was predicted to decrease the activity of the MLH1 protein. The newly identified, functional germline variant was not present in any other CRC patient or control. Thus, a novel germline variant in the MLH1 gene was identified, representing a rare event in sporadic CRC. The occurrence and relevance of this mutation in other types of cancer requires additional investigation.
Keywords: MutL homolog 1; germline mutation; colorectal cancer